Mesquite pods to mezcal : 10,000 years of Oaxacan cuisines - Pérez Rodríguez, Verónica (Associate professor of anthropology); Morell-Hart, Shanti; King, Stacie M. (Linda Schele series in Maya and pre-Columbian studies., 2024)
"This volume explores the roots of traditional Oaxacan food, how it has evolved from its Mixtec origins, and how some traditions exist today; the essays included were written by archaeologists, ethnohistorians, anthropologists, and others with an interest in traditional Oaxacan food"--